Design and development of lactoferrin conjugated lipid-polymer nano-bio-hybrid for cancer theranostics. (June 2022) - Kumar, Rahul; Varshney, Neelima; Mahapatra, Supratim; Mahto, Sanjeev Kumar; Dubey, Vikash Kumar; Chandra, Pranjal
Abstract: In the present investigation, a lactoferrin-conjugated lipid polymer-based nanoparticles (LLPBNPs) encapsulating methotrexate (MTX) as a potential anticancer drugs candidate is constructed via a facile one-step precipitation method. The designed hybrid-nano-bioconjugate exploits both the characteristic features of natural lipids and the biocompatible polymer. The physiochemical properties of the constructed hybrid-nano-bioconjugate were thoroughly characterized by Infrared Spectroscopy, Scanning Electron Microscopy, EDX, Dynamic Light Scattering, and X-ray Diffraction techniques. The general sizes of the particles are obtained in the range of 520–650 nm with a polydispersity of 0.140–0.163 that does not possess a broad size distribution. Further, the analytical encapsulation efficiency of the MTX in LLPBNPs systems was assessed, which was found to be 84.0 ± 1.5%. The in vitro drug release kinetics was analytically examined using the zero and first-order kinetic models. These models revealed that the drug dissociation initially shows the first-order model followed by a sustained rate of drugs delivery. The morphological changes of the nucleus and F-actin cytoskeleton of the cancer cells were studied using molecular binding probes DAPI and rhodamine-conjugated phalloidin, respectively. Graphical Abstract: ga1